Evaluating the Effect of Electrolyte Additive Functionalities on NMC622/Si Cell Performance. Issue 7 (1st July 2022) - Ha, Yeyoung; Martin, Trevor R.; Frisco, Sarah; Rynearson, Leah; Schulze, Maxwell C.; Han, Sang-Don; Trask, Stephen E.; Lucht, Brett L.; Teeter, Glenn; Neale, Nathan R.
Abstract : Unstable electrode/electrolyte interface is the major cause of degradation for silicon (Si)-based anodes for lithium (Li)-ion batteries. Development of functional electrolyte additives can provide a viable path toward stabilizing the dynamic Si/electrolyte interface, which will benefit the development of high energy density Li-ion batteries. Here, we evaluate polymerizable electrolyte additives with varying functional groups (fluorocarbon, thiophosphate, and fluorophosphazene). The additives are examined using LiNi0.6 Mn0.2 Co0.2 O2 /Si full cells where the cycle performance and impedance are measured. Electrochemical tests show that the fluorine-containing additives provide better passivation at the Si electrode, leading to enhanced full cell performance. Among the three additives examined, best electrochemical performance is observed from the fluorocarbon-containing compound, followed by fluorophosphazene- and thiophosphate-containing compounds. Characterization of the solid electrolyte interphase (SEI) on cycled electrodes using Auger electron spectroscopy (AES), X-ray photoelectron spectroscopy (XPS), and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) reveal that higher concentration of fluorine and lithium oxide, and lower concentration of carbonate and organic species correlate with enhanced electrochemical performance.